A Systematic Review and Appraisal of Clinical Practice Guidelines for Musculoskeletal Soft Tissue Injuries and Conditions. (May 2017) - Pincus, Daniel; Kuhn, John E.; Sheth, Ujash; Rizzone, Katie; Colbenson, Kristi; Dwyer, Tim; Karpinos, Ashley; Marks, Paul H.; Wasserstein, David
Background: Clinical practice guidelines (CPGs) are published by several sports medicine institutions. A systematic evaluation can help identify the highest quality CPGs for clinical use and identify any deficiencies that remain. Purpose: To identify and appraise CPGs relevant to clinical sports medicine professionals. Study Design: Systematic review. Methods: Predetermined selection criteria were utilized by 2 reviewers who independently identified published CPGs before January 1, 2014. CPGs were excluded if they focused on injured workers, radiological criteria, medical pathology, or the axial skeleton (back/neck). The remaining guidelines were scored by 6 reviewers with different clinical backgrounds using the Appraisal of Guidelines for Research and Evaluation II (AGREE II). Scores lower than 50% indicated deficiency. Scores were also stratified by the publishing institution and anatomic location and compared using Kruskal-Wallis tests. The Spearman correlation coefficient was used to assess the range of interobserver agreement between the evaluators. Results: Seventeen CPGs met the inclusion criteria. The majority of guidelines pertained to the knee, ankle, or shoulder. Interobserver agreement was strong ( r = 0.548-0.740), and mean total scores between nonsurgical (107.8) and surgical evaluators (109.3) were not statistically different. Overall guideline quality was variable but not deficient for 16 of 17 guidelines (>50%), except regarding clinical "applicability" and "editorial independence." No difference was found between CPGs of the knee, shoulder, foot/ankle, or chronic conditions. However, CPG publishing institutions had significantly different scores; the American Academy of Orthopaedic Surgeons (AAOS) guidelines scored significantly higher (141.4) than the total mean score (108.0). Conclusion: The overall quality of sports medicine CPGs was variable but generally not deficient, except regarding applicability and editorial independence. Bias through poor editorial independence is a concern. To improve future guideline quality, authors should pay particular attention to these areas and use existing highest quality guidelines, or the AGREE II instrument, as templates. CPGs dedicated to anatomic areas other than the knee, ankle, and shoulder are needed.